Performance measurement coffee supply chain on social aspects using the supply chain operations reference (SCOR) approach in the Malang, East Java - Santoso, Imam; Astuti, Retno; Pranowo, Dodyk; Choirun, Annisa’u; Afifah, Yunika Nisa; Maharani, Haqia Sekar; Sinaga, Adello Togario; Wafi’uddin, Izzum; Lu'ayya, Naila Maulidina (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
A performance evaluation system for the coffee supply chain is essential to ensure the sustainability of the coffee industry in the Malang Raya region. This study aimed to design a performance measurement system focusing on the social dimension of the coffee supply chain in Malang Raya, to assess the performance score of each indicator and provide improvement recommendations. The performance evaluation applies the Supply Chain Operations Reference (SCOR) model, with weighting of performance indicators using the Analytical Hierarchy Process (AHP), and normalization of values using the Snorm De Boer method. The Traffic Light System (TLS) is employed to identify priority indicators for improvement. Results from the SCOR-based assessment indicate that Karangploso farmers scored 61.03 (Average), Dampit farmers 70.01 (Good), and Wonosantri farmers 78.32 (Good). The performance score for the roastery was 67.66 (Average), while the coffee industry scored 79.53 (Good). Based on the TLS approach, improvement recommendations for farmers, roasteries, and the coffee industry include enhancing workforce training and skill development, increasing local labor absorption, developing policies to fulfill social standards, expanding strategic partnerships, and promoting the sustainability of the coffee industry through a holistic, multi-stakeholder approach.